Efficacy of Kirschner-wires and tension band in hip arthroplasty for aged patients with unstable intertrochanteric osteoporotic fracture: A 2-to-11-year follow-up. Issue 1 (January 2017) - Zhang, Hua; Xu, Zhongwei; Zhou, Aiguo; Yan, Wenlong; Zhao, Pei; Huang, Xiao; Zhang, Jian
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The aim of this study was to evaluate the efficacy of supplementary fixation in hip arthroplasty with the use of Kirschner-wires and tension band for geriatric patients suffering unstable intertrochanteric osteoporotic fractures. A total of 103 patients aged more than 75 years were recruited. A bipolar or total hip replacement was performed with additional application of Kirschner-wires and tension band, and the participants were followed up for 2 to 11 years. Physical component summary (PCS), mental component summary (MCS), visual analog scale (VAS), and Harris hip score were utilized to evaluate patients' hip pain and function, as well as the mental condition postoperatively after 1.5 months, 3 months, 6 months, 1 year, and annually thereafter until the latest follow-up in 2015. Patients showed a significant improvement in all scores between 1.5 months and 1 year ( P  < 0.001), with the good efficacy lasting at least until the 2-year follow-up. None of the patients showed dislocation, implant loosening, or nonunion of the fracture throughout the follow-up period. In conclusion, it was beneficial to treat unstable intertrochanteric osteoporotic fractures in aged patients with hip arthroplasty coupled with Kirschner-wires and tension band.